PATRON-CLIENT NETWORKS AND PUBLIC UTILITY FOR INCUMBENT POLITICIANS IN ELECTIONS: A BIBLIOMETRIC ANALYSIS - Camico, Danang Bertrand; Salsabila, Muhammad Ihwan; Sihidi, Iradhad Taqwa (Jurnal Dialektika Politik, 2026)
This study analyzes the relationship between patron–client networks and the strategic use of public utilities by incumbent politicians in electoral contexts through a bibliometric approach. It explores how patronage-based electoral strategies are conceptualized and debated within academic literature, particularly regarding the mobilization of state resources to secure voter loyalty and sustain political dominance. The primary objective is to identify patterns of knowledge production, influential scholars, dominant themes, and emerging research trajectories related to incumbency advantage and patronage politics. Methodologically, the study employs bibliometric analysis supported by VOSviewer software to visualize co-occurrence networks among keywords, citation relationships, author collaborations, and leading publication sources. This quantitative mapping enables a systematic understanding of the intellectual structure and evolution of the field. The findings reveal three major thematic clusters. First, political patronage and clientelism are strongly associated with the distribution of public utilities as electoral incentives. Second, incumbency advantage emerges as a central concept linked to resource control and institutional access. Third, social capital and local networks function as mediating mechanisms that strengthen patron–client exchanges. The analysis also shows a growing trend of interdisciplinary research combining political science, governance, and public administration perspectives. Overall, the study demonstrates that public utilities often operate not only as service instruments but also as strategic tools for power reproduction and electoral consolidation.